AB0390 CORRELATION BETWEEN TNF-BLOCKERS BIOAVAILABILITY AND FCGRIIA H131R POLYMORPHISM IN TUNISIAN PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Mahmoud, Ines; Moalla, Myriam; Sfar, Imen; Saidane, Olfa; Tekaya, Aicha Ben; Tekaya, Rawdha; Hamdi, Wafa; Aouini, Saloua; Kchir, Mohamed Montacer; Gorgi, Yousr; Abdelmoula, Leila
Abstract : Background: Rheumatoid arthritis (RA)'s prognosis drastically improved with the introduction of TNF-blockers. However, reasons behind therapeutic failure in some patients remain unclear. Several factors might influence pharmacokinetics of these drugs by reducing their half-life and, consequently, their effectiveness. Considering Fc-containing biologics like infliximab (IFX) and adalimumab (ADL), Fc gamma receptors (FcgRs) polymorphism would be an interesting genetic candidate to focus on. Objectives: The aim of our study was to determine the influence of low affinity allele FcgRIIA-131R on ADL and IFX bioavailability. Methods: We enrolled RA patients treated with IFX and ADL for over six months. Blood samples were collected for each patient immediately prior to drug administration. Quantitative measurements of the residual drug concentration (DC) was carried out by a commercial enzyme-linked immunosorbent assay (ELISA) kit (Promonitor®). Then, we identified patients with DC above therapeutic cut-off (DC+) for each biologic. EULAR criteria were considered to determine treatment outcome. FcgRIIA H131R polymorphism was genotyped using PCR-SSP. Results: Twenty-nine patients were included (13 treated with ADL and 16 with IFX). We identified 31.3% and 23.1% non-responders among patients treated with IFX and ADL respectively. Patients with DC+ were more frequent in ADL group (76.9%) than IFX group (43.75%). For IFX, DC+ was significantly correlated with the presence of FcgRIIA 131-R (p=0.033). In fact, none of the HH-genotyped patients had DC+. Furthermore, an association between FcgRIIA 131-R allele and poor response to IFX was noted (p=0.059) while all HH-genotyped patients responded to IFX. For ADL, no correlation was found with both of residual DC and response to treatment. Conclusion: The presence of FcgIIA-131 R allele might be a predictive factor of non-responsiveness to TNF-blockers. It also appears to be associated to a higher residual DC. That might be explained by a reduced biologic clearance due to a lower binding affinity to Fc portion compared to wild allele FcgRIIA-131H. Therefore, FcgR polymorphism assessment in RA patients would be a decision-making parameter to consider, as part of the personalized medicine approach. References: [1] Montes A, Perez-Pampin E, Narváez J, et al. Association of FCGR2A with the response to infliximab treatment of patients with rheumatoid arthritis. Pharmacogenet Genomics. 2014;24(5):238-245 [2] DávilaáFajardo CL, van der Straaten T, Baak-Pablo R, et al. FcGR genetic polymorphisms and the response to adalimumab in patients with rheumatoid arthritis. Pharmacogenomics. 2015;16(4):373-381 [3] Cañete JD, Suárez B, Hernández MV, et al. Influence of variants of Fc gamma receptors IIA and IIIA on the American College of Rheumatology and European League Against Rheumatism responses to anti-tumour necrosis factor alpha therapy in rheumatoid arthritis. Ann Rheum Dis. 2009;68(10):1547-1552. Disclosure of Interests: None declared